Macroeconomic Fluctuations and the Lorenz Curve - Charles M. Beach (Queen's University, Department of Economics, 1972)
In this paper, a new method is forwarded of estimating the effect of short-run macroeconomic fluctuations on concentration in the size distribution of personal income. In particular, the impacts of changes in unemployment and participation rates and in the level of wage and salary income upon the shape of a Lorenz curve are analysed for each of three age groups in the United States. It is found that increases in the participation rate and decreases in the unemployment rate are consistent with an upward shift of the Lorenz curve, while increases in the overall level of wage and salary income have differing effects on the shape of the Lorenz curve depending on the age and the relative position in the income distribution of a group.
Keywords: 330